Swot Analysis in Improving The Performance of Teaching and Education tt IAIN Pontianak - Rahnang Rahnang; Maladi Maladi (AT-TURATS, 2021)
An overview of the problem of this study is to analyze the performance of IAIN Pontianak sourced from Tri Dharma college. The purpose of this study is: reveal how to maximize strengths, analyze how to minimize weaknesses, reveal how to take advantage of opportunities, and analyze how to anticipate threats to the performance of IAIN Pontianak Education and teaching.   This research is descriptive research with a SWOT analysis approach(Strength, Weaknesses, Opportunities, Threats). Data collection techniques used in the form of free interviews guided to several related informants and documentation techniques in the form of documents and images that are considered important.  This study resulted in potential findings and problems in the performance of IAIN Pontianak starting from 2015-2019. From the results of the identification of potential and problems in the performance of IAIN Pontianak, then studied and analyzed through SWOT analysis. The results obtained, namely: 1)  The strengths that must be maximized so that the performance of IAIN Pontianak increases such as MoU, human resources educators and education personnel, reference collections, communication systems and technology. 2) Weaknesses that must be minimized by IAIN Pontianak, such as the high high high school enthusiasts from Aliyah or pesantren, low curriculum quality, graduation rate has not been maximized  Graduation productivity levels are still not maximal and the placement and management of educators that need to be improved. 3) Opportunities that must be utilized by IAIN Pontianak, such as the interest of SLTA graduates entering IAIN, terse he is a source of research funding from UNDP, Diktis, DIPA IAIN Pontianak, the establishment of cooperation opportunities  between IAIN Pontianak with other universities, the current regulations allow the change of IAIN status to UIN  . 4) The threats that must be anticipated are the proliferation of religious universities, campus promos outside Kalimantan are more attractive, limited funds for the development of sapras and lack of participation of lecturers and education personnel in competency certification  and trainings, spmi functions are less maximal, quotas for receiving research grant funds are few, limited quota of publication of research results.